2003
DOI: 10.1038/nm953
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of human hematopoietic stem cells by direct delivery of the HOXB4 homeoprotein

Abstract: Expansion of human hematopoietic stem cells (HSCs) is a major challenge in cellular therapy, and currently relies on the use of recombinant cytokines or on gene transfer of transcription factors. Of these, the HOXB4 homeoprotein protein is of particular interests as it promotes the expansion of mouse HSCs without inducing the development of leukemia. To eliminate any deleterious effects that might be associated with stable HOXB4 gene transfer into human cells, we took advantage of the ability of HOX proteins t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
196
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 247 publications
(212 citation statements)
references
References 24 publications
5
196
1
6
Order By: Relevance
“…We previously documented that Hoxb4 is among the Hox genes expressed in primitive murine and human hematopoietic cells (Sauvageau et al, 1994;Pineault et al, 2002) and demonstrated that enforced overexpression or direct protein delivery of Hoxb4 is sufficient to stimulate marked HSC expansion in vivo and ex vivo without promoting leukemia (Sauvageau et al, 1995;Antonchuk et al, 2001Antonchuk et al, , 2002Amsellem et al, 2003). These potent effects of Hoxb4 have also been extended to human and nonhuman primate HSCs (Buske et al, 2002;Zhang et al, 2006).…”
Section: Lessons From Hox Overexpression and Knockout Modelsmentioning
confidence: 97%
“…We previously documented that Hoxb4 is among the Hox genes expressed in primitive murine and human hematopoietic cells (Sauvageau et al, 1994;Pineault et al, 2002) and demonstrated that enforced overexpression or direct protein delivery of Hoxb4 is sufficient to stimulate marked HSC expansion in vivo and ex vivo without promoting leukemia (Sauvageau et al, 1995;Antonchuk et al, 2001Antonchuk et al, , 2002Amsellem et al, 2003). These potent effects of Hoxb4 have also been extended to human and nonhuman primate HSCs (Buske et al, 2002;Zhang et al, 2006).…”
Section: Lessons From Hox Overexpression and Knockout Modelsmentioning
confidence: 97%
“…It was also reported that mature osteoblasts derived from an immortalized HM3-B10 MSC line can induce better expansion of multipotent progenitors (MPP), as determined in a long-term culture initiating cell (LTC-IC) assay (Mishima et al 2010). Both growth factor secretions and cell-cell contact have been reported to be needed for the growthmodulatory activates of MSC on HSPC (Flores-Guzman et al 2013;Peled et al 2004;Amsellem et al 2003). Moreover, coculture of HSPC in MSC contact-based cocultures has been shown to improve human chimerism after transplantation (Ferreira et al 2012;Goncalves et al 2006;Walenda et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several labs explored to expand HSPCs with aryl hydrocarbon receptors, copper chelators, stromal support, and automated continuous perfusion of culture systems or "bioreactors" [3,68]. Over-expression of transcription factors, such as SALL4, HOXB4, can also increase the number of HSPCs in vitro [9,10]. Although in vitro culture method for expansion of HSPCs has been improved, it still needs to be optimized to obtain more transplantable HSPCs.…”
mentioning
confidence: 99%